Incidental renal neoplasia following simple nephrectomy of the non-functioning kidney. Is it more common than previously reported? - Shaikh, Waqar Hassan; Sharif, Imran; Khalid, Salman El; Zohaib, Agha; Ahmed , Raja Rizwan; Mithani, Shoaib (International Journal of Endorsing Health Science Research, 2022)
Background: Simple nephrectomy is a technique of removing the kidney from within the gerota’s fascia and is usually for a non-functioning kidney. While for renal tumors, radical nephrectomy is done, which involves the removal of the kidney with gerota’s fascia along with the ureter. Histopathology of patients who undergo simple nephrectomy sometime reveals renal malignancy. Such patients often need further treatment as simple nephrectomy in such cases is mostly suboptimal. The number of studies reporting tumors in simple nephrectomy specimens is limited. We aim to report single-center pathological findings in nephrectomy specimens from patients treated for non-functioning kidneys due to renal stone disease. Methodology: The medical record of patients (n=210) who underwent simple nephrectomy between 2014 and 2021 at the Kidney Centre Postgraduate Training Institute due to renal stone disease was reviewed retrospectively. Results: The total number of patients undergoing simple nephrectomy for non-functioning kidneys due to stone disease was 210. Of those patients, 117 were males, and 93 were females. The mean age was 45.33 ± 17.65 years. The histopathology report of specimens revealed renal malignancy in 10 patients (4.76%), xanthogranulomatous pyelonephritis in 11 patients, tuberculosis of the kidney in 7 patients, and chronic pyelonephritis in 182 patients. Conclusion: In conclusion, the prevalence of renal malignancy in patients undergoing simple nephrectomy is significantly high.